First clinical evidence characterizing safety and efficacy of the new CoCr Biolimus-A9 eluting stent: The Biomatrix Alpha™ registry. (February 2020) - Menown, Ian B.A.; Mamas, Mamas A.; Cotton, James M.; Hildick-Smith, David; Eberli, Franz R.; Leibundgut, Gregor; Tresukosol, Damras; Macaya, Carlos; Copt, Samuel; Sadozai Slama, Sara; Stoll, Hans-Peter
Highlights: First clinical outcomes of a new thin strut cobalt chromium biolimus-eluting stent. The primary endpoint (9 month cardiac death, MI, ciTVR) occurred in 3.9% Cardiac death occurred in 0.8%, MI in 1.1%, and ciTVR in 2.7% Only 1 patient (0.25%) had a definite or probable stent thrombosis. Pre-specified comparison with the LEADERS (BES arm) trial met non-inferiority. Abstract: Background: The biolimus-eluting stent (BES) was the first to elute anti-proliferative drug from a biodegradable polymer. In the randomized LEADERS trial, a stainless steel BES showed non-inferior efficacy compared to a sirolimus-eluting stent and a long-term safety advantage. We report the first clinical efficacy and safety outcomes of a new thin-strut cobalt chromium biolimus-eluting stent (CoCr-BES) from an international multi-centre registry. Methods: We studied 400 all-comer patients with coronary disease receiving CoCr-BES at 12 centres, with follow-up at 9 months and 2 years. The primary endpoint was incidence of major adverse cardiac events (MACE) at 9 months comprising cardiac death, myocardial infarction (MI), and clinically indicated target vessel revascularization (ci-TVR). Key protocol elements were the same as the randomized LEADERS trial to enable a historical control for propensity-matched comparison. Results: Mean patient age was 65 ± 11 years, 19% had diabetes, and 55% presented with unstable angina or MI. On discharge, 96% of patients were on dual antiplatelet therapy (DAPT) and 69% were on DAPT at 9 months. MACE at 9 months occurred in 3.9% of patients, cardiac death in 0.8%, MI in 1.1% and ci-TVR in 2.7%. One patient (0.25%) experienced definite or probable stent thrombosis (ST). A propensity-adjusted comparison showed similar clinical outcomes to the BES arm in the LEADERS trial for the primary endpoint MACE. Conclusions: The new CoCr-BES showed low rates of MACE, MI, ci-TVR and ST at 9 months, similar to the BES arm in LEADERS.